Impacts on Postoperative Bleeding of Surgery for Head and Neck Malignancies While Continuing Antithrombotic Agents - Koji Ushiro; Ryo Asato; Hiroki Ishida; Chisato Chikugo; Yukiko Ito; Takuya Tsuji; Jun Tsuji (International Archives of Otorhinolaryngology)
Introduction Perioperative management of antithrombotic agents may affect bleeding and lead to thromboembolic complications, but there is no consensus on optimal protocol in head and neck surgery.